Educational empowerment for marketing staff: Linking customer relationship orientation, digital banking, and R&D cooperation in Bank BJB - Megantara, Khandinar Shidik; Hurriyati, Ratih; Hendrayati, Heny; Sultan, Mokhamad Adib (ARKA INSTITUTE, 2025)
This study investigates how Customer Relationship Orientation (CRO) and Digital Banking Orientation (DBO) influence Marketing Performance (MP) in Bank BJB, with Marketing Research and Development Cooperation (MRDC) as a moderating variable. Distinct from prior studies, this research introduces an educational perspective emphasizing how marketing staff empowerment through education, digital literacy, and continuous learning strengthens organizational adaptability and competence. Using a quantitative explanatory method, data were collected from 316 marketing personnel proportionally selected from 1,762 employees across Bank BJB’s regional branches. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that both CRO and DBO significantly enhance marketing performance, demonstrating that customer-focused and digitally adaptive strategies are essential for sustaining competitiveness in the banking sector. Moreover, MRDC strengthens these relationships by facilitating the translation of customer insights and technological innovation into more effective marketing strategies. The findings suggest that education-based empowerment, including training in digital banking systems, customer analytics, and R&D collaboration, is vital to develop marketing competence. Therefore, organizational learning and educational interventions should be institutionalized to foster innovation, responsiveness, and long-term performance in the banking sector.